Effect of Obesity on Blood Pressure (International Journal of Physiology, 2019)
BackgroundObesity is a huge problem because it leads to so many complications such as accelerated atherosclerosis, increased incidence of gallbladder disease, type-2 diabetes mellitus, insulin resistance and many carcinomas. One of the major causes for obesity is excess energy intake in food over energy expenditure. Excess weight gain is an important risk factor for hypertension. Hypertension target major organs of the body leading to coronary heart disease, cerebrovascular disease, kidney damage etc. The aim of the study was to investigate the effect of obesity (Body Mass Index(BMI) and Waist Circumference(WC)) on Blood pressure.Materials & MethodEthical committee approval was obtained before starting the study. For this study clinical history was recorded and physical examination including body weight, height, waist&hip circumferences were measured. Waist hip ratio(WHR)was calculated. Blood Pressure was recorded.ResultsObesity was statistically associated with increase in both systolic & diastolic blood pressure.ConclusionThis study revealed that abdominal obesity &increase in BMI were significantly associated with increase in blood pressure.